Binder for catalytic cracking catalyst and preparation method thereof
By using a modified agent containing γ-aluminum-containing aluminum front drives, acid and alkyl ammonium salt, and metal centers in catalytic catalysts, modifiers of polylavic compounds, metal centers, solve the catalyst content and molecular screen content and The problem of deterioration of strength in the volume of the hole realizes the improvement of high -heat wear and the improvement of the pore volume.
Patent Information
- Application Number
- CN202310922362.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-07-26
AI Technical Summary
While the existing catalytic cracking catalysts increase the molecular sieve content and increase the pore volume, their strength becomes worse, resulting in a small pore volume of the catalyst or additive, poor molecular connectivity of reactants, affecting long-term operation.
A binding of a catalytic cracking catalyst, including glue, curing agent, and modifiers. The curing agent is prepared by the γ-aluminum precursor, acid and alkyl ammonium salt. The chelated ligand, the metal centers, the reaction of the metal center, the ethanol and organic acid reaction, the glue includes a phosphorus -containing compound and an aluminum -containing compound.
Improve the thermal wear of catalysts, avoid the rupture of the auxiliary particles, enhance the pore volume and adhesion performance of the adhesive, and improve the resistance and response performance of the catalyst.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst additives, and in particular relates to a binder for a catalytic cracking catalyst and a preparation method thereof. Background Art
[0002] Catalytic cracking catalysts are mainly composed of matrix, active components and binders. The binder not only plays the role of bonding the matrix and active components, but also provides a certain heat capacity during the catalytic cracking reaction. At the same time, the performance of the binder directly affects the physicochemical properties of the catalytic cracking catalyst, such as particle size, wear index, and pore volume. The pores of the catalyst are the site of catalytic reaction and the channel for diffusion and mass transfer. Its pore structure characteristics directly affect the reaction performance such as catalyst activity and selectivity; the wear index of the catalyst has a great influence on the strength of the catalyst carrier, which is easy to cause the carrier to be crushed, resulting in a decrease in the quality of the prepared catalyst. Therefore, the binder directly affects the performance of the catalytic cracking catalyst. When developing catalytic cracking catalysts with higher activity, stronger heavy oil conversion ability, stronger heavy metal resistance, and better coke selectivity, increasing the content of the active component molecular sieve and increasing the micropore volume of the catalytic cracking catalyst often lead to a deterioration in the catalyst's anti-wear performance, resulting in abnormal fluidization, agent running, smoke machine fouling, and increased solid content of oil slurry, which affects the long-term operation of the catalytic cracking unit. At the same time, the accumulation pores between the binders and the corresponding specific surface area become smaller, reducing the diffusion of the reactant macromolecules, resulting in an increase in coke yield and a decrease in the selectivity of the cracking reaction.
[0003] Phosphate is a commonly used binder for catalytic cracking catalysts.
[0004] Patent CN201680055564.2 provides a method for manufacturing a fluid catalytic cracking catalyst additive composition using a new binder. The steps involve mixing an alumina source with water to form a slurry; adding a certain amount of P2O5 source to the alumina slurry; then stirring the slurry and reacting it under controlled temperature and time conditions to form an aluminum phosphate binder; adding zeolite, a certain amount of silica binder and a certain amount of clay to the aluminum phosphate binder; and spray drying the slurry to form catalyst additive particles. The catalyst additive composition contains about 35% to about 65% by weight of zeolite; about 0% to about 10% by weight of silica; about 15% to about 50% by weight of clay, and an aluminum phosphate binder, the aluminum phosphate binder containing about 2.5% to 5% by weight of amorphous or pseudo-boehmite alumina and about 7% to 15% by weight of phosphoric acid.
[0005] Patent US4407730 discloses a catalyst carrier which is basically composed of a magnesium oxide-aluminum oxide-aluminum phosphate matrix after being calcined at 500°C for 10 hours. The average pore size of the carrier is 10-300 angstroms and the specific surface area is 100-350 m2 / g, pore volume 0.3-1.5ml / g, wherein the magnesium oxide content is 0.5 to less than 10mol% or 25-75mol%, the aluminum oxide content is 2-90mol%, and the aluminum phosphate content is 3-95mol%. The preparation method of the catalyst carrier is to mix aluminum nitrate aqueous solution, magnesium nitrate and 85% phosphoric acid solution, then add ammonium hydroxide solution, precipitate under the condition of pH=9, filter, dry and roast at 500℃ for about 10h. The catalytic cracking catalyst prepared by mixing the catalyst carrier with zeolite has high gasoline selectivity and can be used as a catalyst for cracking high metal content raw materials.
[0006] Patent US5286369 discloses a catalytic cracking method for hydrocarbon feedstock, which comprises reacting a hydrocarbon feedstock under catalytic cracking process conditions and in the presence of a catalyst, wherein the catalyst comprises a zeolite selected from ultrastable Y zeolite, ZSM-5 zeolite, Beta zeolite, SAPO zeolite, ALPO zeolite and a crystalline aluminum phosphate binder, wherein the specific surface area of the crystalline aluminum phosphate binder is less than 20 m2 / g and the pore volume is less than 0.1 ml / g. An aluminum salt solution of the catalyst, preferably an aluminum nitrate solution containing 9-61% of Al(NO3)3·9H2O2, is mixed with a phosphoric acid solution, especially a phosphoric acid solution containing 20-86% by weight of phosphoric acid, a pH value of 0.5-0.9 and a molar ratio of aluminum to phosphorus of 0.4-1.4, to obtain an aluminum phosphate solution. The obtained aluminum phosphate solution is mixed with a slurry of zeolite (such as Beta zeolite) and clay (preferably kaolin) to obtain a spray-dryable slurry with a solid content of 20-45 wt%, which contains 8-25 wt% of aluminum phosphate, 10-40 wt% of zeolite and 35-82 wt% of clay on a dry basis. The slurry is spray-dried at 200-400° C. During the drying process, the aluminum phosphate solution is converted into a binder.
[0007] Patent CN102049284B discloses a catalytic cracking propylene additive, which contains 30-80% by weight of molecular sieves, wherein the content of ZSM-5 zeolite is 28-78% by weight, and the content of clay is 10-65% by weight. The additive contains P, which is 5.0-20.0% by weight, preferably 7.0-15.0% by weight, in terms of P2O5, and the content of La2O3 is 0-1.0% by weight. Aluminum phosphate sol is used as a binder to improve the wear resistance of the additive, increase the solid content of the spray slurry, and avoid the chlorine content on the spray slurry and the additive. The prepared catalytic cracking propylene additive has significantly improved activity, and when used in combination with the main catalyst, the activity of the main catalyst is reduced less, the product distribution can be improved, and it has good dry gas and coke selectivity, while increasing the propylene yield and the gasoline octane number.
[0008] Patent CN102847547B discloses an inorganic binder containing phosphorus aluminum compounds and a preparation method thereof, wherein the binder contains 15-40 wt% Al2O3, 45-80 wt% P2O5 and 1-40 wt% clay, wherein the P / Al weight ratio is 1-6, the pH value is 1-3.5, and the solid content is 15-60 wt%. The preparation method comprises: dispersing aluminum hydroxide and / or aluminum oxide and clay that can be colloided by acid with decationized water into a slurry with a solid content of 15-45 wt%, adding concentrated phosphoric acid to the slurry at a weight ratio of P / Al=1-6 under stirring, and then reacting at 50-99°C for 15-90 minutes. The preparation method provided by the present invention can avoid the curing of the binder caused by the uneven local instantaneous violent reaction of the material, the exothermic overtemperature, and the obtained binder can improve the wear resistance, activity and selectivity of the FCC catalyst.
[0009] Patent CN1957070A discloses that a catalyst composition comprising a metal phosphate binder and a zeolite can be used to increase the olefin yield in a cracking process. The composition generally also comprises aluminum phosphate, and the metal in the metal phosphate is a metal other than aluminum. Depending on the selected metal, the yield of propylene and isobutylene in a fluid catalytic cracking process can be increased compared to a catalyst that does not contain such a metal phosphate binder. The catalyst may also comprise a non-zeolitic molecular sieve, thereby making the catalyst composition suitable for use in fields other than catalytic cracking, such as purification and adsorption applications.
[0010] Patent CN1291915A provides a method for improving the catalytic activity of small-pore and medium-pore acidic zeolite catalysts, the method comprising the following steps: treating zeolite with a phosphorus compound to form a phosphorus-treated zeolite, and combining the phosphorus-treated zeolite with AlPO4. Optionally, the phosphorus-treated zeolite can be calcined. Optionally, after the step of combining zeolite with AlPO4, the combined catalyst is steamed. Examples of phosphorus-containing compounds that can be used to treat zeolite include phosphoric acid, aluminum hydrogen phosphate or aluminum dihydrogen phosphate, organic phosphites and organic phosphorus. Preferred phosphorus-containing compounds are acid aluminum phosphate. Another embodiment provides a method for improving the wet heat stability of a zeolite catalyst, the method comprising the following steps: first treating zeolite with a phosphorus-containing compound, then mixing with AlPO4.
[0011] Patent CN101376830A discloses a hydroprocessing catalyst carrier and a preparation method thereof. The carrier contains alumina fiber and a phosphorus additive, wherein the phosphorus additive is partially or completely introduced in the form of aluminum dihydrogen phosphate. The addition of alumina fiber and aluminum dihydrogen phosphate to the carrier during the preparation process can improve the mechanical strength and wear resistance of the carrier, thereby improving the mechanical strength and wear resistance of the catalyst, improving the stability of the catalyst, and at the same time extending the service life of the catalyst and reducing production costs. The carrier is used as a carrier of an ebullating bed hydroprocessing catalyst. When used to treat heavy fractions, it can remove nitrogen, sulfur and other heteroatoms in oil products to the maximum extent and reduce the olefin and aromatic content thereof.
[0012] Patent CN1957070A discloses an inorganic binder containing phosphorus aluminum compounds and a preparation method thereof, wherein the binder contains 15-40 wt% Al2O3, 45-80 wt% P2O5 and 1-40 wt% clay, wherein the P / Al weight ratio is 1-6, the pH value is 1-3.5, and the solid content is 15-60 wt%. The preparation method comprises: dispersing aluminum hydroxide and / or aluminum oxide and clay that can be colloided by acid with decationized water into a slurry with a solid content of 15-45 wt%, adding concentrated phosphoric acid to the slurry at a weight ratio of P / Al=1-6 under stirring, and then reacting at 50-99°C for 15-90 minutes. The preparation method provided by the present invention can avoid the curing of the binder caused by the uneven local instantaneous violent reaction of the material and the exothermic overtemperature, and the obtained binder can improve the wear resistance, activity and selectivity of the FCC catalyst.
[0013] Patent CN1132897C discloses a catalytic cracking catalyst containing phosphorus and zeolite, which contains zeolite, clay and binder, wherein the catalyst also contains a phosphorus and aluminum additive uniformly dispersed in the catalyst, based on the total weight of the catalyst, the content of zeolite is 25-70 weight %: the content of clay is 5-55 weight %: the content of binder is 5-50 weight %: the content of phosphorus and aluminum additive is 0.5-20 weight % based on the solid content of the additive. The phosphorus and aluminum additive is a reaction product obtained by reacting phosphoric acid solution with aluminum oxide and / or hydroxide, the specific gravity of which is 1.2-1.7 g / ml, and the atomic ratio of phosphorus to aluminum is greater than 1 to 12. The catalyst has higher anti-wear strength.
[0014] As mentioned above, the phosphate aluminum sol (or aluminum phosphate solution) used in the prior art is prepared by reacting a phosphorus compound with an aluminum sol or a silica sol under the condition of controlling pH>3; or, it is prepared by precipitating a phosphoric acid solution of aluminum nitrate and magnesium nitrate with an ammonium hydroxide solution under the condition of pH=9; or, it is prepared by precipitating a solution containing phosphoric acid and rare earth ions with an alkaline solution; or, it is prepared by precipitating a solution containing aluminum ions and phosphate and hydrogen phosphate with an alkaline solution; or, an ammonium salt selected from phosphoric acid, ammonium orthophosphate and ammonium salt of hypophosphoric acid and a phosphorus compound of phosphoric acid are directly added to a slurry containing silicon oxide, clay and zeolite; or, an aluminum phosphate solution with a pH of 0 to 1 is directly added to a slurry containing silicon oxide, clay and zeolite. When the catalyst is prepared by the above method, although the wear resistance of the catalyst can be increased to a certain extent, when the molecular sieve content in the catalyst is high or the catalyst pore volume is large, its wear resistance is still insufficient, especially after high-temperature steam aging, the situation is worse. Summary of the invention
[0015] The purpose of the present invention is to provide a binder for catalytic cracking catalysts to solve the problems that the strength of existing catalytic cracking catalysts and additives deteriorates while increasing the molecular sieve content and pore volume, the catalyst or additive has a small pore volume, and the reactant molecule has poor connectability.
[0016] Another object of the present invention is to provide a method for preparing a binder for a catalytic cracking catalyst.
[0017] To achieve the above-mentioned purpose, the present invention provides a binder for a catalytic cracking catalyst, comprising a rubber material, a curing agent and a modifier, wherein the curing agent is prepared by hydrothermal reaction of a γ-alumina precursor, an acid and an alkyl ammonium salt; the modifier is prepared by reaction of a multidentate chelating ligand, a metal center ligand, ethanol and an organic acid; and the rubber material comprises a phosphorus-containing compound and an aluminum-containing compound.
[0018] The binder of the catalytic cracking catalyst of the present invention has a peptization index of ≤50% of the γ-alumina precursor. In the present invention, the XRD spectrum of the γ-alumina precursor with a peptization index of ≤50% has characteristic peaks at 2θ of 14±1°, 28±1°, 38±1°, and 49±1°, such as pseudo-boehmite, boehmite, and the like.
[0019] In the binder of the catalytic cracking catalyst of the present invention, the multidentate chelate ligand is a didentate chelate ligand having at least two coordinating atoms, and the coordinating atoms are P, O or N, O, preferably the coordinating atoms are P and O.
[0020] The binder of the catalytic cracking catalyst described in the present invention, the multidentate chelating ligand is one or more of aminotri (methylene phosphonic acid), hydroxyethylidene diphosphonic acid, ethylenediamine tetra (methylene phosphonic acid), diethylenetriamine penta (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, 2-hydroxyphosphonoacetic acid, bis (1,6-hexamethylenetriamine penta (methylene phosphonic acid), hexamethylenediamine tetra (methylene phosphonic acid), ethylenediamine tetraacetic acid, diethylenetriamine pentaacetic acid and 1,2-ethylenediamine.
[0021] The binder of the catalytic cracking catalyst of the present invention, the metal center ligand comprises rare earth metal and transition metal.
[0022] In the binder of the catalytic cracking catalyst of the present invention, the rare earth metal is one or more of lanthanum, cerium, neodymium and samarium; the transition metal is one or more of copper, silver, nickel, zinc, cobalt and cadmium. In the present invention, the dosage ratio of various metal ions in the metal center ligand is not specifically limited and can be adjusted according to actual conditions. The molar ratio of transition metal to rare earth metal recommended by the present invention is 5 to 10:1.
[0023] The binder of the catalytic cracking catalyst of the present invention, the metal center ligand is a chloride or nitrate of a rare earth metal or a transition metal.
[0024] The binder of the catalytic cracking catalyst of the present invention, the organic acid in the modifier is one or more of benzoic acid, lactic acid, propionic acid, formic acid, acetic acid, sorbic acid and malic acid.
[0025] The binder of the catalytic cracking catalyst of the present invention, the molar ratio of the acid to the γ-alumina precursor in the curing agent is 0.1-1:1, preferably 0.2-0.5:1; the mass ratio of the γ-alumina precursor to the alkyl ammonium salt is 9-20:1, wherein the γ-alumina precursor is calculated as alumina. There is no restriction on the type of acid in the curing agent, and any inorganic acid or organic acid commonly used in the industry can be used; such as HCl, HNO3, H2SO4, HCOOH, CH3COOH, etc. can meet the requirements.
[0026] The binder of the catalytic cracking catalyst described in the present invention, the alkyl ammonium salt is not specifically limited, and the conventional alkyl ammonium salt in the industry can be used. The present invention recommends that the alkyl ammonium salt is one or more of cetyltrimethylammonium bromide CTAB, cetylpyridinium chloride CPC and dimethyldioctadecylammonium chloride.
[0027] In the binder of the catalytic cracking catalyst of the present invention, the molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound in the sizing material is 1 to 10:1, preferably 2 to 6:1.
[0028] The aluminum-containing compound and the phosphorus-containing compound described in the present invention are not specifically limited, and conventional ones in the industry can be used. The aluminum-containing compound includes but is not limited to aluminum oxides, aluminum hydroxides, aluminum-containing organic compounds, etc., such as aluminum oxide, aluminum hydroxide, boehmite sodium aluminate, aluminum chloride, aluminum isopropoxide, etc.; preferably aluminum oxides and aluminum hydroxides. The phosphorus-containing compound includes but is not limited to phosphorus oxides, phosphorus oxyacids, phosphoric acid, phosphates or phosphorus-containing organic matter, etc., such as phosphoric acid, diammonium hydrogen phosphate, phosphorus pentoxide, organic phosphonic acid, sodium phosphate, calcium phosphate. Preferably, phosphorus oxyacids, phosphoric acid, and phosphorus-containing ammonium salts.
[0029] The binder of the catalytic cracking catalyst of the present invention, based on the dry basis mass of the binder as 100%, has a sizing agent content of 70-94wt%, preferably 76-88wt%; a curing agent content of 4-20wt%, preferably 8-16wt%; and a modifier content of 2-10wt%, preferably 4-8wt%.
[0030] The binder of the catalytic cracking catalyst of the present invention has a molar ratio of the multi-dentate chelate ligand in the modifier to the metal ion in the metal center ligand of 2-5:1.
[0031] To achieve the above object, the present invention also provides a method for preparing a binder for a catalytic cracking catalyst, comprising the following steps:
[0032] S1: mixing a γ-alumina precursor with an acid, then adding an alkyl ammonium salt solution to react, and after the reaction is completed, performing a hydrothermal treatment to obtain a curing agent;
[0033] S2: mixing the multi-dentate chelating ligand and the organic acid solution to prepare an organic acid solution of the multi-dentate chelating ligand, adding the ethanol solution, and mixing evenly to prepare a multi-dentate chelating ligand solution;
[0034] S3: adding the metal center ligand to the organic acid solution, adding the ethanol solution after it is completely dissolved, and mixing well to obtain the metal center ligand precursor solution;
[0035] S4: adding equal volumes of the multi-dentate chelating ligand solution and the metal center ligand precursor solution into a high shear dispersing emulsifier, maintaining the temperature at 30-50° C., and adjusting the pH value of the system to 5-8; after the reaction is completed, a multi-metal composite chelating modifier solution is obtained;
[0036] S5: adding the aluminum-containing compound and the phosphorus-containing compound into a high shear dispersing emulsifier and mixing them with the multi-metal composite chelating modifier solution, adding water to ensure the fluidity of the material in the high shear dispersing emulsifier, and controlling the pH of the system to 5-7 and the temperature of the system to 60-80° C. to allow the reaction to be fully achieved;
[0037] S6: adding the curing agent obtained in step S1 into a high shear dispersing emulsifier to react. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0038] In the present invention, when the added phosphorus-containing compound used in step S5 is not acidic, an acid can be added to adjust the pH of the system to ≤7. The specific type of acid is not limited, and any conventional inorganic acid or organic acid in the industry can be used, such as hydrochloric acid, nitric acid, phosphonic acid, etc.
[0039] The preparation method of the binder of the catalytic cracking catalyst of the present invention comprises the following steps: in step S1, the mixing conditions of the γ-alumina precursor and the acid are as follows: mixing at 30-100°C for 10-120min, adding the alkyl ammonium salt solution and reacting at 30-100°C for 15-30min; the hydrothermal treatment temperature is 400-1000°C, the volume content of water vapor is 10-80%, preferably 20-60%, and the time is 1-10h, preferably 4-6h.
[0040] In the method for preparing a binder for a catalytic cracking catalyst of the present invention, in step S2, the mass concentration of organic acid in the multidentate chelate ligand solution is 10-30%, the mass concentration of ethanol is 5-20%, and the molar concentration of the multidentate chelate ligand is 0.2-1.0 mol / L.
[0041] In the method for preparing the binder of the catalytic cracking catalyst of the present invention, in step S3, the mass concentration of the organic acid in the metal center ligand precursor solution is 10-30%, and the mass concentration of ethanol is 5-20%.
[0042] The binder provided by the present invention can be applied to catalytic cracking catalysts, catalytic cracking catalysts or additives.
[0043] It has been found that when the molecular sieve content in the additive prepared by the existing aluminum-phosphorus sol is high or the pore volume of the additive is large, the additive particles are prone to different degrees of rupture. It is speculated that since the existing aluminum-phosphorus sol contains too much chlorine, ammonium, nitrate and other ions, these ions are likely to have a certain stable combination with the components that play a bonding role, so that the components that play a bonding role are in an inactive state. During the preparation of the additive, it is still in this inactive state, so that, on the one hand, this stable combination reduces the bonding effect of the components that play a bonding role, and on the other hand, during the spray drying process of the additive, especially during the water vapor aging process, the chlorine, ammonium, and nitrate that have a stable combination with the bonding component become unstable, and generate hydrogen chloride, ammonia, nitrogen, oxygen and other gases respectively. The generation of these gases generates a large number of "bubbles" inside the additive particles. When the temperature rises, these bubbles will rush out from the inside of the additive, resulting in damage to the shape of the additive particles. In severe cases, it causes the rupture of the additive particles, thereby reducing the bonding effect of various binders and greatly reducing the anti-wear performance of the additive.
[0044] In the binder of the catalytic cracking catalyst provided by the present invention, a metal center ligand composed of a multi-dentate chelate ligand and a plurality of metals is introduced. Under the promotion of organic acid and ethanol, a multi-metal chelate modifier can be prepared in situ during the preparation of the binder. Compared with directly using commercially available metal chelates, the in-situ prepared multi-metal chelate modifier has better water solubility, can promote the combination of the modifier and the phosphorus aluminum sol, and has a better modification effect; on the other hand, the multi-dentate chelate ligand can be chelated with a variety of metal ions to form a multi-metal chelate ligand, reducing the dissolution problem between different solvents during the preparation of the binder, and reducing the interaction between different chelate ligands; at the same time, the ratio of different metals can be flexibly controlled to achieve the effect of accurately regulating the performance of the binder; again, the method of preparing a multi-metal chelate modifier in situ can break the limitation of the small number of commercially available metal chelates and expand the applicability of binder preparation. Finally, it is preferred to use a multi-dentate chelate ligand with N, P, and O as the coordinating atoms to reduce the introduction of too many heteroatoms into the binder, affect the performance of the binder, and reduce the impact on the performance of the catalyst.
[0045] The binder of the catalytic cracking catalyst provided by the present invention introduces an in-situ prepared multi-metal chelate modifier to improve the properties of the phosphate binder. The transition metal ions, alkali metals, and light rare earth metal ions in the multi-metal chelate can strengthen the interaction between aluminum phosphate and the curing agent and improve the strength. Experiments show that the modification of the composite metal ions can greatly improve the thermal collapse phenomenon under high-temperature hydrothermal conditions and significantly improve the thermal wear performance of the catalyst; at the same time, it can avoid the premature hardening of the colloid during the catalyst molding and drying process, and increase the pore volume of the binder after curing. A large number of test results show that the addition of the multi-metal chelate modifier can form micropores and mesopores inside the binder during the preparation process without affecting the bonding performance of the binder.
[0046] The binder of the binder of the catalytic cracking catalyst provided by the present invention adopts a low peptization index γ-alumina precursor in the curing agent, which, on the one hand, reduces the peptization of the γ-alumina precursor by the acidic medium during the preparation process, accurately controls the presence of free metallic aluminum in the catalyst system, avoids excessive reaction with the effective components of the binder, and affects the bonding performance of the binder. The small amount of peptized γ-alumina precursor can react with the phosphorus-containing compound in the sizing material under specific conditions to form a binder. On the other hand, the γ-alumina precursor with a low peptization index can form a large number of mesopores during the curing process, thereby increasing the pore volume of the binder after curing.
[0047] The preparation method of the high-strength, large-pore volume phosphorus-containing binder provided by the present invention is to add a γ-alumina precursor and perform hydrothermal treatment on the material under hydrothermal conditions, so that the crystal structure of the γ-alumina precursor partially collapses under highly harsh conditions, and re-crystallizes, further increasing the pore volume and pore size of the γ-alumina precursor, increasing the number of mesopores on the γ-alumina precursor, and at the same time, adjusting the surface structure of the γ-alumina precursor, providing a favorable place and environment for the attachment of metal ions in the subsequent modifier. On the other hand, the γ-alumina precursor is used as a curing agent for the aluminum phosphate binder to increase the pore volume and improve the bonding strength. Pre-treating the γ-alumina precursor with an alkyl ammonium salt before hydrothermal treatment can make the pore expansion of the γ-alumina precursor during the hydrothermal treatment more efficient, and the obtained pore size distribution is more concentrated in the mesopore range, eliminating large pores above 20nm, and improving the pore volume of the binder while improving the bonding performance of the binder.
[0048] The preparation method of the high-strength, large-pore volume phosphorus-containing binder provided by the present invention adopts a high-shear emulsification reactor, which can disperse the low-peptization index γ-alumina precursor into a uniform and viscous emulsion slurry, overcoming the technical difficulty that the low-peptization index γ-alumina precursor has poor solubility and cannot form a uniform slurry. On the other hand, the application of the high-shear emulsification reactor solves the problem that the multi-metal chelate and the aluminum phosphate binder cannot be fully mixed, promotes the mutual reaction between the binder and the multi-metal chelate, effectively regulates the microenvironment such as the supersaturation distribution in the reactor, and improves the role of the binder modification component. DETAILED DESCRIPTION
[0049] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0050] If no specific experimental steps or conditions are specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.
[0051] The raw materials and equipment involved in the present invention are all commercially available and can meet the implementation of the technical solution of the present invention. However, for the convenience of comparison, the following raw materials are used in the following examples:
[0052] Y-type molecular sieve and aluminum sol were collected from Lanzhou Petrochemical Company;
[0053] Pseudoboehmite, boehmite and boehmite are produced by the Shandong Aluminum Plant of Aluminum Corporation of China;
[0054] Kaolin was produced by China Kaolin Co., Ltd.;
[0055] Formic acid, acetic acid, propionic acid, benzoic acid, oxalic acid, lactic acid, citric acid, nitric acid, hydrochloric acid, cetyltrimethylammonium bromide (CTAB), cetylpyridinium chloride, dimethyldioctadecylammonium chloride, 1,2-ethylenediamine, ethylenediaminetetraacetic acid, hydroxyethylidene diphosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, lanthanum chloride, cerium nitrate, neodymium sulfate, samarium chloride, copper nitrate, silver nitrate, zinc sulfate, nickel chloride, aluminum trioxide, aluminum hydroxide, aluminum isopropoxide, aluminum chloride, aluminum sulfate, phosphorus pentoxide, phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate were all analytically pure and produced by Sinopharm Group.
[0056] Example 1
[0057] In the binder provided in this embodiment, based on the binder dry basis as 100%, the content of the sizing agent is 70wt%, the content of the curing agent is 20wt%, and the content of the modifier is 10wt%. The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 2:1. The specific preparation method is as follows:
[0058] S1: Pseudo-boehmite with a peptization index of 50% is mixed with deionized water, hydrochloric acid is added, and the molar ratio of hydrochloric acid to pseudo-boehmite (calculated as alumina) is 0.1:1, and the mixture is reacted at 30°C for 2 hours, and a cetyltrimethylammonium bromide (CTAB) solution is added, and the mixture is reacted at 30°C for 30 minutes; then, a hydrothermal treatment is performed at 400°C and a water vapor content of 10% for 10 hours to obtain curing agent particles; wherein the mass ratio of pseudo-boehmite to CTAB is 9:1;
[0059] S2: Mix the bidentate chelating ligand 1,2-ethylenediamine with formic acid solution to prepare an organic acid solution of a multidentate chelating ligand. After mixing evenly, add ethanol solution to prepare a 1,2-ethylenediamine ligand solution, wherein the molar concentration of 1,2-ethylenediamine is 0.2 mol / L, the mass concentration of the organic acid in the solution is 30%, and the mass concentration of ethanol is 20%.
[0060] S3: Add lanthanum chloride and copper nitrate to formic acid solution, add ethanol solution after they are completely dissolved, mix them evenly to obtain a mixed metal center ligand precursor solution. The mass concentration of formic acid in the precursor solution is 30%, the mass concentration of ethanol is 20%, the molar concentration of mixed metals in the precursor solution is 0.1 mol / L, and the molar ratio of lanthanum chloride to copper nitrate is 1:5.
[0061] S4: Add the 1,2-ethylenediamine ligand solution obtained in S2 and the metal-containing center ligand precursor solution obtained in S3 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 50°C, add ammonia water to adjust the pH value of the system to 8, and react for 30 minutes to obtain a multi-metal composite chelating modifier solution.
[0062] S5: Add aluminum oxide and phosphorus pentoxide (P / Al molar ratio is 1:1) into a high shear dispersing emulsifier and mix with the multi-metal composite chelating modifier solution, add an appropriate amount of water to ensure that the binder has good fluidity, and add hydrochloric acid (concentration 38%) to adjust the pH of the system to 7. Maintain the system temperature at 60°C and react for 20 minutes.
[0063] S6: Add the curing agent prepared in S1 to the mixed slurry described in S5 to carry out a reaction at a temperature of 60° C. for 30 minutes. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0064] Example 2
[0065] In the binder provided in this embodiment, based on the binder dry basis as 100%, the content of the sizing agent is 94wt%, the content of the curing agent is 4wt%, and the content of the modifier is 2wt%. The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 5:1. The specific preparation method is as follows:
[0066] S1: mixing boehmite with a peptization index of 30% with deionized water, adding oxalic acid, the molar ratio of oxalic acid to pseudo-boehmite (calculated as alumina) is 1:1, reacting at 100°C for 10 minutes, adding cetylpyridinium chloride (CPC) solution, reacting at 100°C for 15 minutes; then hydrothermally treating at 1000°C with a water vapor content of 80% for 1 hour to obtain curing agent particles; wherein the mass ratio of pseudo-boehmite to CPC is 20:1;
[0067] S2: Mix the hexadentate chelating ligand ethylenediaminetetraacetic acid with the acetic acid solution to prepare the acetic acid solution of the ethylenediaminetetraacetic acid multidentate chelating ligand, and add the ethanol solution after mixing evenly to prepare the ethylenediaminetetraacetic acid ligand solution, wherein the molar concentration of the ethylenediaminetetraacetic acid is 1 mol / L, the mass concentration of the organic acid in the solution is 10%, and the mass concentration of the ethanol is 5%.
[0068] S3: Add cerium nitrate and silver nitrate to acetic acid solution, add ethanol solution after they are completely dissolved, mix them evenly to obtain a mixed metal center ligand precursor solution. The mass concentration of acetic acid in the precursor solution is 10%, the mass concentration of ethanol is 5%, the molar concentration of the mixed metal in the precursor solution is 0.2 mol / L, and the molar ratio of cerium nitrate to silver nitrate is 1:10.
[0069] S4: Add the ethylenediaminetetraacetic acid ligand solution obtained in S2 and the metal center ligand precursor solution obtained in S3 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 30°C, add ammonia water to adjust the pH value of the system to 5, and react for 50 minutes to obtain a multi-metal composite chelating modifier solution.
[0070] S5: Add aluminum hydroxide and phosphoric acid (P / Al molar ratio of 10:1) into a high shear dispersing emulsifier and mix with the multi-metal composite chelating modifier solution, add an appropriate amount of water to ensure that the binder has good fluidity, adjust the pH value of the system to 5 according to the actual pH value of the mixed solution, maintain the system temperature at 80°C, and react for 10 minutes.
[0071] S6: Add the curing agent prepared in S1 to the mixed slurry described in S5 to carry out a reaction at a temperature of 80° C. for 10 minutes. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0072] Example 3
[0073] In the binder provided in this embodiment, based on 100% dry basis of the binder, the content of the sizing agent is 76wt%, the content of the curing agent is 16wt%, and the content of the modifier is 8wt%. The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 3:1.
[0074] The specific preparation method is as follows:
[0075] S1: Boehmite with a peptization index of 20% is mixed with deionized water, nitric acid is added, and the molar ratio of nitric acid to boehmite (calculated as alumina) is 0.2:1, and the mixture is reacted at 80°C for 30 minutes, and dimethyl dioctadecyl ammonium chloride solution is added, and the mixture is reacted at 80°C for 15 minutes; then, the mixture is hydrothermally treated at 800°C and a water vapor content of 20% for 6 hours to obtain curing agent particles; wherein the mass ratio of boehmite to dimethyl dioctadecyl ammonium chloride is 14:1;
[0076] S2: Mix the tetradentate chelating ligand hydroxyethylidene diphosphonic acid with the propionic acid solution to prepare a propionic acid solution of the hydroxyethylidene diphosphonic acid multidentate chelating ligand. After mixing evenly, add the ethanol solution to prepare a hydroxyethylidene diphosphonic acid ligand solution. The molar concentration of hydroxyethylidene diphosphonic acid is 0.6 mol / L, the mass concentration of the organic acid in the solution is 20%, and the mass concentration of ethanol is 10%.
[0077] S3: Add neodymium sulfate and nickel sulfate to propionic acid solution, add ethanol solution after they are completely dissolved, mix them evenly to obtain a mixed metal center ligand precursor solution. The mass concentration of propionic acid in the precursor solution is 20%, the mass concentration of ethanol is 10%, the molar concentration of mixed metals in the precursor solution is 0.2 mol / L, and the molar ratio of neodymium chloride to nickel nitrate is 1:8.
[0078] S4: Add the hydroxyethylidene diphosphonic acid ligand solution obtained in S2 and the metal center ligand precursor solution obtained in S3 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, and react for 40 minutes to obtain a multi-metal composite chelating modifier solution.
[0079] S5: Add aluminum isopropoxide and ammonium dihydrogen phosphate (P / Al molar ratio is 2:1) into a high shear dispersing emulsifier and mix with the multi-metal composite chelating modifier solution, add an appropriate amount of water to ensure that the binder has good fluidity, adjust the pH value of the system to 6.0, maintain the temperature at 70°C, and react for 15 minutes.
[0080] S6: Add the curing agent prepared in S1 to the mixed slurry described in S5 to carry out a reaction at a temperature of 70° C. for 20 minutes. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0081] Example 4
[0082] In the binder provided in this embodiment, based on 100% dry basis of the binder, the content of the sizing agent is 88wt%, the content of the curing agent is 8wt%, and the content of the modifier is 4wt%. The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 3:1.
[0083] The specific preparation method is as follows:
[0084] S1: Pseudo-boehmite with a peptization index of 20% is mixed with deionized water, citric acid is added, and the molar ratio of citric acid to pseudo-boehmite (calculated as alumina) is 0.5:1, and the mixture is reacted at 60°C for 1 hour, and a mixed solution of dimethyldioctadecylammonium chloride and hexadecyltrimethylammonium bromide (CTAB) is added, and the mixture is reacted at 80°C for 20 minutes; then, the mixture is calcined at 600°C and a water vapor content of 60% for 4 hours to obtain curing agent particles; wherein the mass ratio of pseudo-boehmite to dimethyldioctadecylammonium chloride to hexadecyltrimethylammonium bromide (CTAB) is 28:1:1;
[0085] S2: Mix the tetradentate chelating ligand hexamethylenediaminetetramethylenephosphonic acid with benzoic acid solution to prepare a benzoic acid solution of hexamethylenediaminetetramethylenephosphonic acid multidentate chelating ligand, mix well and add ethanol solution to prepare a hexamethylenediaminetetramethylenephosphonic acid ligand solution, the molar concentration of hexamethylenediaminetetramethylenephosphonic acid is 0.6 mol / L, the mass concentration of organic acid in the solution is 20%, and the mass concentration of ethanol is 10%.
[0086] S3: Add samarium chloride and zinc nitrate to benzoic acid solution, add ethanol solution after complete dissolution, mix well to obtain mixed metal center ligand precursor solution. The mass concentration of benzoic acid in the precursor solution is 20%, the mass concentration of ethanol is 10%, the molar concentration of mixed metal in the precursor solution is 0.2 mol / L, and the molar ratio of samarium chloride to zinc nitrate is 1:6.
[0087] S4: Add the hexamethylenediaminetetramethylenephosphonic acid ligand solution obtained in S2 and the metal center ligand precursor solution obtained in S3 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, and react for 40 minutes to obtain a multi-metal composite chelating modifier solution.
[0088] S5: Add aluminum isochloride and ammonium dihydrogen phosphate (P / Al molar ratio is 6:1) into a high shear dispersing emulsifier and mix with the multi-metal composite chelating modifier solution, add an appropriate amount of water to ensure that the binder has good fluidity, adjust the pH value of the system to 6.0, maintain the temperature at 70°C, and react for 15 minutes.
[0089] S6: Add the curing agent prepared in S1 to the mixed slurry described in S5 to carry out a reaction at a temperature of 70° C. for 20 minutes. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0090] Example 5
[0091] In the binder provided in this embodiment, based on 100% dry basis of the binder, the content of the sizing agent is 82wt%, the content of the curing agent is 10wt%, and the content of the modifier is 8wt%. The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 3:1.
[0092] The specific preparation method is as follows:
[0093] S1: Pseudo-boehmite with a peptization index of 20% is mixed with deionized water, sulfuric acid is added, the molar ratio of hydrochloric acid to pseudo-boehmite (calculated as alumina) is 0.3:1, the reaction is carried out at 70°C for 1 hour, a mixed solution of cetylpyridinium chloride (CPC) and cetyltrimethylammonium bromide (CTAB) is added, the mass ratio of cetylpyridinium chloride (CPC) to cetyltrimethylammonium bromide (CTAB) is 1:1, and the reaction is carried out at 70°C for 30 minutes; then, a hydrothermal treatment is carried out at 700°C and a water vapor content of 50% for 5 hours to obtain curing agent particles; wherein the mass ratio of pseudo-boehmite, dimethyl dioctadecyl ammonium chloride and CTAB is 20:1:1;
[0094] S2: The octadentate chelating ligand diethylenetriaminepenta(methylenephosphonic acid) is mixed with the lactic acid solution to prepare a lactic acid solution of the diethylenetriaminepenta(methylenephosphonic acid) multidentate chelating ligand. After mixing evenly, an ethanol solution is added to prepare a diethylenetriaminepenta(methylenephosphonic acid) ligand solution. The molar concentration of the diethylenetriaminepenta(methylenephosphonic acid) is 0.6 mol / L, the mass concentration of the organic acid in the solution is 20%, and the mass concentration of the ethanol is 10%.
[0095] S3: Add lanthanum chloride and cadmium nitrate to the lactic acid solution, add ethanol solution after they are completely dissolved, mix them evenly to obtain a mixed metal center ligand precursor solution. The mass concentration of lactic acid in the precursor solution is 20%, the mass concentration of ethanol is 10%, the molar concentration of the mixed metal in the precursor solution is 0.2 mol / L, and the molar ratio of lanthanum chloride to cadmium nitrate is 1:8.
[0096] S4: Add the diethylenetriamine penta(methylenephosphonic acid) ligand solution obtained in S2 and the metal center ligand precursor solution obtained in S3 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, and react for 40 minutes to obtain a multi-metal composite chelating modifier solution.
[0097] S5: Add aluminum hydroxide and diammonium hydrogen phosphate (P / Al molar ratio of 5:1) into a high shear dispersing emulsifier and mix with the multi-metal composite chelating modifier solution, add an appropriate amount of water to ensure that the binder has good fluidity, adjust the pH value of the system to 6.0, maintain the temperature at 70°C, and react for 15 minutes.
[0098] S6: Add the curing agent prepared in S1 to the mixed slurry described in S5 to carry out a reaction at a temperature of 70° C. for 20 minutes. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0099] Example 6
[0100] The raw materials, contents and preparation methods of each composition of Example 6 and Example 5 are the same, except that:
[0101] 1) The multidentate chelating ligand is aminotri(methylenephosphonic acid);
[0102] 2) The transition metal in the metal ligand in the colloidal modifier is a mixture of cobalt and copper, and the rare earth metal is a mixture of lanthanum and cerium, wherein the molar ratio of cobalt: copper: lanthanum: cerium is 8:8:1:1.
[0103] Comparative Example 1
[0104] Aluminum sol and pseudo-boehmite are used as binders. The mass ratio of aluminum sol to pseudo-boehmite is 1:2 based on aluminum oxide, and the peptization index of pseudo-boehmite is 99%. Pseudo-boehmite is mixed with 25wt% hydrochloric acid, peptized at 60°C for 30 minutes, and then mixed with aluminum sol to obtain the binder. The mass ratio of pseudo-boehmite (based on aluminum oxide) to hydrochloric acid is 1:0.2.
[0105] Comparative Example 2
[0106] This comparative example is similar to Example 5, except that no curing agent and modifier are included.
[0107] Aluminum hydroxide and diammonium hydrogen phosphate (P / Al molar ratio of 5:1) and an appropriate amount of water were added to a high shear dispersing emulsifier to ensure that the binder has good fluidity. The pH value of the system was adjusted to 6.0, the temperature was maintained at 70°C, and the reaction was carried out for 15 minutes.
[0108] Comparative Example 3
[0109] This comparative example is similar to Example 5, except that no curing agent is included and an equal amount of pseudo-boehmite is used instead.
[0110] In the binder provided in the comparative example, based on 100% of the binder dry basis, the content of the sizing agent is 82wt%, the content of the pseudo-boehmite is 12wt%, and the content of the modifier is 6wt%. The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 3:1.
[0111] The specific preparation method is as follows:
[0112] S1: The octadentate chelating ligand diethylenetriaminepenta(methylenephosphonic acid) is mixed with a lactic acid solution to prepare a lactic acid solution of a diethylenetriaminepenta(methylenephosphonic acid) multidentate chelating ligand. After mixing evenly, an ethanol solution is added to prepare a diethylenetriaminepenta(methylenephosphonic acid) ligand solution. The molar concentration of the diethylenetriaminepenta(methylenephosphonic acid) is 0.6 mol / L, the mass concentration of the organic acid in the solution is 20%, and the mass concentration of the ethanol is 10%.
[0113] S2: Add lanthanum chloride and cadmium nitrate to lactic acid solution, add ethanol solution after complete dissolution, mix well to obtain mixed metal center ligand precursor solution. The mass concentration of lactic acid in the precursor solution is 20%, the mass concentration of ethanol is 10%, the molar concentration of mixed metal in the precursor solution is 0.2 mol / L, and the molar ratio of lanthanum chloride to cadmium nitrate is 1:8.
[0114] S3: Add the diethylenetriamine penta(methylenephosphonic acid) ligand solution obtained in S1 and the metal center ligand precursor solution obtained in S2 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, and react for 40 minutes to obtain a multi-metal composite chelating modifier solution.
[0115] S4: Add aluminum hydroxide and diammonium hydrogen phosphate (P / Al molar ratio is 5:1) into a high shear dispersing emulsifier and mix with the multi-metal composite chelating modifier solution, add an appropriate amount of water to ensure that the binder has good fluidity, adjust the pH value of the system to 6.0, maintain the temperature at 70°C, and react for 15 minutes. The binder of the catalytic cracking catalyst is obtained.
[0116] Comparative Example 4
[0117] This comparative example is similar to Example 5, except that the modifier in Example 5 is replaced by lanthanum chloride and cadmium nitrate in this comparative example. The contents of lanthanum chloride and cadmium nitrate in this comparative example are the same as those in Example 5.
[0118] In the binder provided in this comparative example, based on 100% dry basis of the binder, the content of the sizing agent is 82 wt%, the content of the curing agent is 12 wt%, and the content of the modifiers lanthanum chloride and cadmium nitrate (calculated as metal oxide) is 6 wt%.
[0119] The specific preparation method is as follows:
[0120] S1: Pseudo-boehmite with a peptization index of 20% is mixed with deionized water, hydrochloric acid is added, and the molar ratio of hydrochloric acid to pseudo-boehmite (calculated as alumina) is 0.3:1, and the mixture is reacted at 70°C for 1 hour, and a mixed solution of dimethyldioctadecylammonium chloride and hexadecyltrimethylammonium bromide (CTAB) is added, and the mixture is reacted at 70°C for 30 minutes; then, the mixture is hydrothermally treated at 700°C and a water vapor content of 50% for 5 hours to obtain curing agent particles; wherein the mass ratio of pseudo-boehmite, dimethyldioctadecylammonium chloride and CTAB is 20:1:1;
[0121] S2: Add aluminum hydroxide and diammonium hydrogen phosphate (P / Al molar ratio of 5:1) into a high shear dispersing emulsifier and add an appropriate amount of water to ensure that the binder has good fluidity. The pH value of the system is adjusted to 6.0, the temperature is maintained at 70°C, and the reaction is carried out for 15 minutes.
[0122] S3: Add lanthanum chloride and cadmium nitrate into a high shear dispersing emulsifier and mix with the rubber material, and the molar ratio of lanthanum chloride to copper nitrate is 1:8.
[0123] S4: Add the curing agent prepared in S1 to the mixed slurry described in S3 to carry out a reaction at a temperature of 70° C. for 20 minutes. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
[0124] Experimental example
[0125] The binders prepared in Examples 1 to 5 and Comparative Examples 1 to 4 are used to replace the binder materials such as aluminum sol, silica sol, pseudo-boehmite, etc. in the production process of conventional catalytic cracking catalysts, respectively, and the catalytic cracking catalyst is prepared according to 35% (mass percentage) of ultra-stable Y-type molecular sieve, 23% (mass percentage) of binder, 42% (mass percentage) of kaolin, and a solid content of 35% (mass percentage). The specific method is as follows:
[0126] First, kaolin and deionized water were mixed and slurried, and then a binder and a Y-type molecular sieve slurry were added, and the catalyst slurry was obtained after being stirred evenly, and then spray-molded and dried. The spray molding conditions were that the furnace temperature of the spray tower was controlled at 580° C. and the spray tail gas temperature was controlled at 160° C. After the obtained catalyst was calcined at 500° C. for 1 hour, an ammonium chloride salt solution was used for ion exchange to obtain the catalyst described in the embodiment.
[0127] The binders prepared in the above embodiments and comparative examples were used to prepare catalysts according to the above method, and the physical and chemical properties were tested according to the following evaluation and analysis methods. The specific results are shown in Table 1.
[0128] Evaluation and analysis methods:
[0129] The surface area of the catalyst was determined by low-temperature nitrogen adsorption-desorption method (NB / SH / T 0959);
[0130] The pore volume of the catalyst was tested using the water drop method (NB / SH / T 0955);
[0131] The catalyst wear index was determined using the straight tube method (NB / SH / T 0964);
[0132] The thermal collapse rate of the catalyst is tested on a laboratory small fixed fluidized bed (all parts are made of stainless steel) wear system. During the experiment, the catalyst in the fluidized bed is continuously fluidized and worn under the action of fluidized air or water vapor. The extremely fine powder particles under wear flow out of the fluidized bed through the filter element with the gas, and the larger particles are blocked by the filter element and remain in the fluidized bed to continue to wear. There are 5 air inlet holes evenly distributed at the front end and around the air guide pipe, with an aperture of 1mm, and the filtration accuracy of the filter element is 1μm. The specific steps are as follows: first weigh 100g of the prepared catalyst, recorded as w1, and then add it to the fluidized bed, raise the temperature of the preheater to 150℃, the fluidized bed temperature to 200℃, turn on the air generator, adjust the gas flow rate to 40m / s, and the superficial gas velocity in the reactor to 0.8m / s. After fluidized attrition for 4h, weigh the remaining catalyst mass in the reactor and record it as w2. Change the preheater temperature to 650℃, the fluidized bed temperature to 680℃, and keep other conditions unchanged to repeat the measurement of the remaining catalyst weight, recorded as w3, then the thermal collapse rate L is:
[0133] L=(w2-w3) / w2×100%
[0134] The catalyst reaction performance was tested on a small fixed fluidized bed microreactor according to the NB / SH / T0952-2017 method.
[0135] Table 1
[0136] Wear index, m% Pore volume, ml / g <![CDATA[Specific surface area, m 2 / g]]> Thermal collapse rate, m% Micro-reactive, m% Example 1 1.4 0.40 292 5.2% 67 Example 2 0.8 0.35 263 6.9% 63 Example 3 1.0 0.39 279 5.6% 66 Example 4 0.8 0.36 268 6.1% 63 Example 5 0.9 0.38 274 5.8% 64 Example 6 0.9 0.38 273 5.9% 64 Comparative Example 1 1.9 0.32 242 8.6% 60 Comparative Example 2 1.2 0.29 234 11.4% 58 Comparative Example 3 9.5 0.31 256 5.8% 62 Comparative Example 4 1.1 0.37 255 9.9% 62
[0137] It can be seen from the data in the above table that, relative to the comparative example, the catalyst prepared by using the binder and preparation method described in the present invention instead of traditional aluminum sol and acidified pseudo-boehmite still has high wear resistance, pore volume and specific surface area based on the content of high molecular sieve.
[0138] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A binder for a catalytic cracking catalyst, characterized in that: The invention comprises a rubber compound, a curing agent and a modifier, wherein the curing agent is prepared by hydrothermal reaction of a γ-alumina precursor, an acid and an alkyl ammonium salt; the modifier is prepared by reaction of a multi-dentate chelating ligand, a metal center ligand, ethanol and an organic acid; and the rubber compound comprises a phosphorus-containing compound and an aluminum-containing compound.
2. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The peptization index of the γ-alumina precursor is ≤50%.
3. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The multidentate chelate ligand is a didentate chelate ligand having at least two coordinating atoms, and the coordinating atoms are P, O or N, O, preferably the coordinating atoms are P and O.
4. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The multidentate chelating ligand is one or more of aminotri (methylene phosphonic acid), hydroxyethylidene diphosphonic acid, ethylenediamine tetra (methylene phosphonic acid), diethylenetriamine penta (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, 2-hydroxyphosphonoacetic acid, bis (1,6-hexamethylenetriamine penta (methylene phosphonic acid), hexamethylenediamine tetra (methylene phosphonic acid), ethylenediamine tetraacetic acid, diethylenetriamine pentaacetic acid and 1,2-ethylenediamine.
5. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The metal center ligands include rare earth metals and transition metals.
6. The binder for catalytic cracking catalyst according to claim 5, characterized in that: The rare earth metal is one or more of lanthanum, cerium, neodymium and samarium; the transition metal is one or more of copper, silver, nickel, zinc, cobalt and cadmium.
7. The binder for catalytic cracking catalyst according to claim 5, characterized in that: The metal center ligand is a chloride or nitrate of a rare earth metal or a transition metal.
8. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The organic acid in the modifier is one or more of benzoic acid, lactic acid, propionic acid, formic acid, acetic acid, sorbic acid and malic acid.
9. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The molar ratio of the acid to the γ-alumina precursor in the curing agent is 0.1 to 1:1, preferably 0.2 to 0.5:1; the mass ratio of the γ-alumina precursor to the alkylammonium salt is 9 to 20:1, wherein the γ-alumina precursor is calculated as alumina.
10. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The alkylammonium salt is one or more of cetyltrimethylammonium bromide (CTAB), cetylpyridinium chloride (CPC) and dimethyldioctadecylammonium chloride.
11. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound in the rubber material is 1 to 10:1, preferably 2 to 6:
1.
12. The binder for catalytic cracking catalyst according to claim 1, characterized in that: Taking the dry basis mass of the binder as 100%, the content of the sizing agent is 70-94wt%, preferably 76-88wt%; the content of the curing agent is 4-20wt%, preferably 8-16wt%; the content of the modifier is 2-10wt%, preferably 4-8wt%.
13. The binder for catalytic cracking catalyst according to claim 1, characterized in that: The molar ratio of the multidentate chelating ligand in the modifier to the metal ion in the metal center ligand is 2-5:
1.
14. The method for preparing a binder for a catalytic cracking catalyst according to any one of claims 1 to 13, characterized in that: The following steps are involved: S1: mixing a γ-alumina precursor with an acid, then adding an alkyl ammonium salt solution to react, and after the reaction is completed, performing a hydrothermal treatment to obtain a curing agent; S2: mixing the multi-dentate chelating ligand and the organic acid solution to prepare an organic acid solution of the multi-dentate chelating ligand, adding the ethanol solution, and mixing evenly to prepare a multi-dentate chelating ligand solution; S3: adding the metal center ligand to the organic acid solution, adding the ethanol solution after it is completely dissolved, and mixing well to obtain the metal center ligand precursor solution; S4: adding equal volumes of the multi-dentate chelating ligand solution and the metal center ligand precursor solution into a high shear dispersing emulsifier, maintaining the temperature at 30-50° C., and adjusting the pH value of the system to 5-8; after the reaction is completed, a multi-metal composite chelating modifier solution is obtained; S5: adding the aluminum-containing compound and the phosphorus-containing compound into a high shear dispersing emulsifier and mixing them with the multi-metal composite chelating modifier solution, adding water to ensure the fluidity of the material in the high shear dispersing emulsifier, and controlling the pH of the system to 5-7 and the temperature of the system to 60-80° C. to allow the reaction to be fully achieved; S6: adding the curing agent obtained in step S1 into a high shear dispersing emulsifier to react. After the reaction is completed, a binder for the catalytic cracking catalyst is obtained.
15. The method for preparing a binder for a catalytic cracking catalyst according to claim 14, characterized in that: In step S1, the mixing conditions of the γ-alumina precursor and the acid are as follows: mixing at 30-100°C for 10-120 minutes, adding the alkyl ammonium salt solution and reacting at 30-100°C for 15-30 minutes; the temperature of the hydrothermal treatment is 400-1000°C, the volume content of water vapor is 10-80%, preferably 20-60%, and the time is 1-10 hours, preferably 4-6 hours.
16. The method for preparing a binder for a catalytic cracking catalyst according to claim 14, characterized in that: In step S2, the mass concentration of organic acid in the multidentate chelating ligand solution is 10-30%, the mass concentration of ethanol is 5-20%, and the molar concentration of the multidentate chelating ligand is 0.2-1.0 mol / L.
17. The method for preparing a binder for a catalytic cracking catalyst according to claim 14, characterized in that: In step S3, the mass concentration of the organic acid in the metal center ligand precursor solution is 10-30%, and the mass concentration of ethanol is 5-20%.
Citation Information
Patent Citations
Hydrotreating catalyst carrier and preparation thereof
CN101376830A
Catalytic cracking propylene additive and preparation method thereof
CN102049284B
Inorganic binder containing phosphorus and aluminum compounds
CN102847547B
Fcc catalyst additive and binder
CN108025298A
Catalytic cracking catalyst containing phosphorus and zeolite and its preparing method
CN1132897C
Cited By
High-strength and large-pore-volume phosphorus-containing binder as well as preparation method and application thereof
CN118106018A
High-strength, large-pore-volume phosphorus-containing binder, its preparation method and application
CN118106018B